Identification of poisonous plants in the heart of public squares of ribeirão Preto SP - Romani, G. N. [UNESP]; Batista, G. S. [UNESP]; Gobi, J. [UNESP]; Gimenes, R. [UNESP]; Ferraz, M. V. [UNESP]; Pivetta, K. F L [UNESP] (My University, 2013)
Toxic plants, many ornamentals, may be present in gardens, backyards, parks, vases, squares and vacant lots around the cities. Some of these plants are well known and exuberant, with strong color and decorative aspects, but when swallowed or handled, can cause severe intoxication specially in children. The main objective was to identify the poisonous plants found in public squares of Ribeirão Preto downtown, among five squares: XV de Novembro Square, Carlos Gomes Square, Bandeiras Square, Luís de Camões Square and Sete de Setembro Square. In this study, a literature review was performed in order to know the species that have been recorded as toxic plant. For the species in question, the common name and therapeutic indication were recorded. Over all evaluated squares toxic species were found. Sete de Setembro Square was the most frequent species in a total of seven toxical species. The most common species in the surveyed places were: Euphorbia pulcherrima, Buxus semprevirens and Dracaena fragrans, popularly known as Poinsettia, Boxwood and Cornstalk Dracaena, respectively. The importance of doing studies in urban squares is to improve care to ensure the afforestation process of the cities.
Keywords: Poisonous plants; Toxic elements; Urban afforestation